Seroprevalence and trend of Hepatitis B virus infection among the blood donors of North Karnataka: A Nine Year Study - Dr. Sujata S. Giriyan; Dr. Niraj Kumar Nirala; Dr. Akansha Agrawal; Dr. Richa Bajpai (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Hepatitis B is one of the leading transfusion transmissible infections. The prevalence of this infection varies across the different geographical areas with intermediate prevalence in India. Studying the trend in seroprevalence is useful to assist the preventive strategies. The aim of this study was to determine the trend of seroprevalence of hepatitis B in North Karnataka region over a nine-year period (2007-2015). Materials & Methodology: The study was conducted at one of the largest blood banks of Northern Karnataka of an apex health care institution serving predominantly the people of North Karnataka. A retrospective analysis of blood donors over a period of nine years (2007-2015) was done to assess the seroprevalence and the trend of hepatitis B infection among them. ELISA was used to detect the hepatitis B surface antigen in the donors as a marker of infection. Results: A total of 80,312 blood donors were undertaken for the study. About 1613 (2%) were positive for HBsAg, which falls under the “intermediate prevalence (2%-7%) zone” as per World Health Organization (WHO) guidelines. An increasing trend in first five years (2007-2011) and then decreasing trend over next four years (2012-2015) was observed in the present study. Replacement donors and male blood donors showed significantly higher seropositivity compared to voluntary donors and female donors respectively. Conclusion: North Karnataka has an intermediate prevalence of hepatitis B in blood donors with increasing trend in initial five years and decreasing trend over the last four-year period.